Influence of bisphosphonate therapy on bone geometry, volumetric bone density and bone strength of femoral shaft in postmenopausal women with rheumatoid arthritis. Issue 1 (December 2016) - Meinen, Rahel; Galli-Lysak, Inna; Villiger, Peter; Aeberli, Daniel
Abstract Background There is evidence that postmenopausal women with rheumatoid arthritis (RA) on glucocorticoid (GC) therapy and bisphosphonate (BP) have an increased risk for atypical subtrochanteric and atypical diaphyseal femoral fracture (AFF). The underlying mechanism has not been elucidated so far. Using peripheral quantitative computed tomography (pQCT), the aim of the present study was to compare bone geometry, volumetric bone mineral density (vBMD) and bone strength of femoral shaft in BP-treated and BP-naïve postmenopausal women with RA. Methods Prospective cross-sectional pQCT scans were taken at 33 % of total femur of BP-treated and BP-naïve RA patients. Bone parameters of the two groups were compared and correlated to disease characteristics and muscle cross-sectional area (CSA). Results A total of 60 consecutive postmenopausal RA patients, 20 with BP therapy and 40 BP-naïve, were included in the study. The median age of the subjects was 63.5 years (range 48–85 years), and median disease duration (RA) was 12.0 years (range 2–47 years). Height and weight of the patients of the two groups were comparable. Women in the BP group were on average 4.3 years older (p  = 0.044), and duration since menopause was on average 5.76 years longer (p  = 0.045). In the BP group, there was a 13.31 % reduced muscle cross-sectional area around the proximal thigh (p  = 0.013); cortical CSA was smaller by 5.3 % (p  = 0.043); however, total and medullary CSA, as well as cortical vBMD and the polar bone stress–strain index of the femoral shaft were similar in the two groups. In regression analysis, age, time since menopause and muscular CSA were significant factors determining cortical CSA, cortical thickness and femoral index (p  < 0.05). Regression model showed no significant effect of BP therapy on bone geometry and density of the femoral diaphysis at 33 %. Conclusion Differences in cortical CSA between BP-treated and BP-naïve postmenopausal RA patients were found to be associated only with differences in age, time since menopause and muscle cross-sectional area around the proximal thigh. In interpreting our results, it should be kept in mind that BP was given only to patients with increased fracture risk. This fact might have a confounding effect on our findings of differences between the two groups.